Strict Liability as an Expansion of the Meaning of Criminal Acts in Environmental Crimes - Maulana, Aby; Azmi, Nurul; Luthfie Hakim, Muhammad; Noor Prasetyo, Said (KnE Social Sciences, 2024)
The problems in overcoming criminal acts in the environmental sector not only need practice but also need development and improvement in theoretical studies, so that the purpose of the laws and regulations formed reaches their goals. One of the interesting discussions to be reviewed in depth is the applicability of the concept of strict liability or absolute responsibility in enforcing criminal law in the environmental sector, as regulated in Article 88 of Law Number 32 of 2009 concerning environmental protection and management. Strict liability in general is to put criminal liability to the perpetrator of a criminal act without the necessity of guilt. In other words, errors with the concept of strict liability can be ruled out. Eliminating wrongdoing does not mean eliminating evidence for criminal acts that have indeed been committed. The conduct of a criminal act is the basis on which a person can be held criminally liable (determining the presence or absence of a mistake). However, in the concept of strict liability, this does not apply on the contrary, a person who has committed a criminal act has also been fulfilled with the element of guilt, so it does not need to be proven or ruled out. The criminal act becomes completed, and the element of guilt is evidenced by the loss arising as a result of the criminal act committed. Keywords: strict liability, criminal acts, environmental crime 1.